A study of vehicles operation ref: Intergrated Forwarding & Shipping Sendirian Berhad / Ramli Abdullah - Abdullah, Ramli (1992)
Time is critical. This is a phrase that is always used by transport companies. Timing is critical especially for trailers in transit as it may cause goods to be delayed. Transport costs constitute a major portion of distribution expenses, compared to storage, unit load and administration. Savings (e.g through lowering of rates) can be of substantial benefit for manufacturers. Product pricing at retail level take into account costs of distribution (where tranport cost is significant). A lowering of overall distribution cost may precipitate a fall in retail price, hence benefiting the consumer. Manufacturers also gain through the opportunity for greater sales. The need to be competetive in the market place constitutes an important objective to tranport operators. Successful 1 competition is in making products available, at the right time to the right place in a good condition. Physical Distribution Management is an integral element within transport management. Transportation is simply that part of PDM concerned with making the phsical delivery of a service to a customer. (vii) Due to the tremendous development in Integrated Forwarding & Shipping Sdn. Bhd. and the increment in the number of lorries used in the company,various problems arose in vehicle operation as a result from limited staffs and electronic equipment. Therefore, this study will look at the present vehicle movement. It is hoped that the study will able to come out with recommendations and solutions to improve the present situation. Personnel Management ♦= Transport Management Phyaical Distribution Management